HUBUNGAN KELINCAHAN TUBUH (AGILITY) TERHADAP KECEPATAN REAKSI (REACTION) PENJAGA GAWANG SEPAKBOLA PADA TIM TARUNA FC & RUMBAI FC KECAMATAN RUMBAI PESISIR PEKANBARU - Angga Buswira Yanto; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The purpose of this research is to find out and prove that there is a the correlation of agility to the reaction speed of the fottball goalkeeper on Taruna FC & Rumbai FC team Rumbai Pesisir sub-district of Pekanbaru. As for the type of research used is the type of correlation research, this research is a correlational research by comparing the results of measurement of two different variables in order to find the level of correlation between these variables. The population in this research amounted to 47 people from the Taruna FC team of 22 people & 25 people from the Rumbai FC team. Because in this research using a sampling technique that is Purposive Sampling which is a technique of determining the sample based on consideration of the objectives set by the researcher, therefore taking until Purposive Sampling does not pay attention to the principle of representation of the population. With this, the researchers took a sample of 6 people who were only positioned as goalkeepers, namely 2 people from the Taruna FC team & 4 people from the Rumbai FC team. Then test the data using normality test, data normality test with liliefors test, correlation analysis. Test for normality of variables X L₀max (0.289) < Ltable (0.319), normality test for variable Y L₀maks (0, 122) < Ltable (0.319). With that data is normally distributed and the research conclusions address where the hypothesis is accepted at a significant level α = 0.05 in other words there is a the correlation of agility to the reaction speed of the fottball goalkeeper on Taruna FC & Rumbai FC team Rumbai Pesisir sub-district of Pekanbaru with r count (0.881) > r table (0.811).Key Words: Body Agility, Speed of Goalkeeper Reaction, Soccer